2020
DOI: 10.21467/preprints.157
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Overview of the Current and Potential Effects of COVID-19 on U.S. Animal Shelters

Abstract: Despite the global COVID-19 pandemic, animal shelters in the United States and around the world are experiencing massive increases in adoption and foster rates.  Remaining open as designated essential businesses, these shelters are interviewing adopters in parking lots to maintain social distancing guidelines and watching even long-term or hard-to-adopt residents find permanent homes.  The reasons behind these phenomena are varied, but appear to stem in part from the positive benefits humans feel that they rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…In the first months of COVID-19 pandemic, animal shelters globally experienced an increase in adoption and foster rates [ 20 ], however, in the survey only two respondents re-homed their cat (one permanently). It may be that people who disposed their cat were not inclined to fill out a survey.…”
Section: Discussionmentioning
confidence: 99%
“…In the first months of COVID-19 pandemic, animal shelters globally experienced an increase in adoption and foster rates [ 20 ], however, in the survey only two respondents re-homed their cat (one permanently). It may be that people who disposed their cat were not inclined to fill out a survey.…”
Section: Discussionmentioning
confidence: 99%
“…Shelters could also have implemented changes that were not captured by this survey. For example, some shelters have suggested that conducting meet-and-greets with prospective adopters in the carpark, rather than the shelter environment, was beneficial for long-term animals with poor kennel behavior as it potentially increased their chances of adoption [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Animal shelters that were not obligated to accept domestic rabbits may have declined new intakes to minimize disease spread in shelter and to protect resident rabbits, resulting in a decrease in rabbit intakes. Furthermore, it has been reported in Canada and the US that the COVID-19 pandemic may have decreased overall animal intakes [ 3 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rabbits that entered the shelter in 2020 and 2021 experienced a shorter LOS than rabbits that entered the shelter in 2017, 2018, and 2019 ( Fig 4 ). The reduced LOS in 2020 and 2021 might be attributed to the impact of the COVID-19 pandemic on public interest in animal adoptions [ 31 , 34 ]. For example, Morgan and colleagues [ 34 ] surveyed a national pet adoption website in Isarel and found an increased interest in dog adoptions and adoption rate and a decrease in LOS as social isolation measures tightened during the pandemic.…”
Section: Discussionmentioning
confidence: 99%